'n Model vir psigiatriese verpleegkundige begeleiding van die pasiënt met geestesongemak: Deel II - M. Greeff (AOSIS, 1993)
The conceptualization of the concept mental discomfort formed only part of the research methodology. The goal was to conceptualize the concept mental discomfort in the conceptual frame of reference of Psychiatric Nursing. The concept was one of three concepts to be analyzed in this research. The combined approach of concept analysis was used. This was done as follows: • Research dictionary and subject terminological definitions of the concept; • Construct cases of the concept: a model and borderline case; • Formulate criteria for the concept; • Conduct internal dialogue; • Reformulate and refine the concept. After completion of the process the concept mental discomfort was conceptually defined.